Good Corporate Governance Practices in Managing Finance at Islamic Institutions in Indonesia - Asrida, Asrida; Yenti, Elfina; Asmadia, Tezi; Emrizal, Emrizal; Ayu, Suci Putri (International Journal of Multidisciplinary Research of Higher Education, 2025)
Financial management at Sharia Financial Institutions certainly requires the application of good corporate governance principles so that transparency, accountability, so that the distribution of funds can be carried out fairly and on target. This study aims to analyze how financial management in one of the Sharia Financial Institutions in Indonesia is based on the principles of good corporate governance. The research method used is qualitative with a case study model. Data sources consist of primary data and secondary data. Primary data was obtained through interviews with ten informants consisting of leaders and employees at the Sharia Financial Institution, while secondary data came from official reports and information published through the official website of the Sharia Financial Institution. All data were analyzed thematically using the Milles and Hubberman model. The results showed that financial management in Sharia Financial Institutions has applied the principles of Good Corporate Governance with five levels of optimization of the principles, namely; i) the principle of transparency, ii) the principle of accountability, iii) the principle of responsibility, iv) the principle of independence, v) the principle of equality and fairness. With the optimal application of good corporate governance principles, financial management in sharia institutions can run more effectively in improving the welfare of beneficiaries.